ANALYSIS OF INTERNAL CONTROL STRUCTURE ON CASH DISBURSEMENTS AT ABC HOTEL MEDAN, INDONESIA - Zufrizal (CV. Radja Publika, 2023)
This study aims to determine whether the systems and procedures for cash disbursements accounting information systems in conformity with the rules. This study also aims to determine the effectiveness of the internal control structure of cash disbursements. Cash is the most liquid financial asset used for company operations and pays company’s liability. Cash is the only asset that is ready to be converted into other types of assets. Cash is very easy to hide, carry and most risky to fraudulent activities. The cash disbursement accounting information system is a system that receives special attention in terms of monitoring assets in a company. The research was conducted at ABC Hotel Medan, Indonesia. The study was conducted by taking the data used for the study include the systems and procedures expenditure cycle. The data have been analyzed with descriptive methods with qualitative approach, this study intends to make a picture of a situation or event, and compares the systems and procedures for cash disbursements at ABC Hotel with the rules set. The results showed that the cash disbursement accounting information system at ABC Hotel was generally adequate associated with the characteristics of the internal control structure.